Model kekuatan geser dan kekuatan tarik perlekatan copper alloy dengan resin akrilik setelah tin plating (Tensile strength and shear strength models bonds in between copper alloy and acrylic resin after tin plating) - Endanus Harijanto; Sri Yogyarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Tooth crown restoration was made in a complex system consisting of several elements, namely tensile strength and shear strength bond between copper alloy and acrylic resin after tin plating. The aim of this exemination was to find a model representing connection between tensile strength and shear strength in between copper alloy with acrylic resin in statistic method. In conclusion, this exemination utilizing a strength model = 0.645 + 1.237 × tensile strength resulted shear strength exemination. On the other hand, the utilization of a strength = –0.506 + 0.808 × shear strength resulted tensile strength exemination.